Women's attitudes towards negotiating safe sexual practices in Nigeria: Do family structure and decision-making autonomy play a role? - Chukwuechefulam Kingsley Imo; Clifford O. Odimegwu; Nicole De Wet-Billings (BMC, 2022)
Abstract Background The risk of contracting sexually transmitted infections (STIs), including human immunodeficiency virus (HIV) is related to women's sexual attitudes, beliefs, and power dynamics within marriages in developing countries. Despite the interventions towards improving women's sexual health and well-being, women are disproportionately affected by the risk of STIs transmission compared with their male counterparts in most sub-Saharan African countries including Nigeria. This study examined the roles of family structure and decision-making autonomy on women's attitudes towards negotiating safe sexual practices in Nigeria. Methods The study involved analyses of data from a nationally representative and weighted sample size of 28,219 ever-married/cohabiting women aged 15-49 years from the 2018 Nigeria Demographic and Health Survey. Descriptive and statistical analyses were carried out, including frequency tables, Pearson's chi-square test, and multivariable binary logistic regression model. Results The overall prevalence of having positive attitudes towards negotiating safe sexual practices were 76.7% and 69.6% for a wife justified in asking the husband to use a condom if he has an STI and refusing to have sex with the husband if he had sex with other women, respectively. The results further showed that polygamous unions negatively influenced urban and rural women's attitudes towards negotiating safe sexual practices, but women's decision-making autonomy on how to spend their earnings was found to be a protective factor for having positive attitudes towards negotiating safe sexual practices with partners. Surprisingly, there were significant variations in attitudes towards negotiating safe sexual practices among urban and rural women who enjoyed decision-making autonomy on their healthcare (aOR 1.70; CI 1.32-2.18 and aOR 0.52; CI 0.44-0.62, respectively). Plausibly, such women might have constrained them to compromise their sexual relationships for fear of being neglected by partners. Conclusion The outcomes of this study have some policy implications for both maternal and child health. There is the need to intensify programmes aimed at improving women's sexual health and rights towards achieving sustainable development goals of preventing deaths of newborns, ending STIs and creating gender in Nigeria.